Pengaruh Kepemilikan Manajerial, Struktur Modal, Kinerja Keuangan Terhadap Nilai Perusahaan (Property dan Real Estate) - Fazdlilah Adri; Desmiyawati '; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted to analyze the effect of managerial ownership, capital structure and financial performance the corporate value of the property & real estate company listed on the Indonesia Stock Exchange.The population in this study is the property & real estate companies in Indonesia Stock Exchange (IDX). Observation period is 2010 to 2012. According to the data from the Indonesia Stock Exchange there are 52 property & real estate company during the period of observation. The technique to determination of sample is purposive sampling method, where the sample set by using certain criteria. Based on these criteria there are 49 (forty nine) companies that fulfill the criteria above. Analysis of data using multiple regression methods. Managerial ownership has no significant effect on firm value. Capital structure (Debt to Equity Ratio) has a significant effect on firm value. Financial performance (return on assets ratio) has a significant effect on firm value.Keywords: Managerial Ownership, Capital Structure, Financial Performance, Corporate Value